Ion gradients and fluxes in isolated liver cells - Sainsbury, G; Gillian McNeill Sainsbury (1978)
The overall aim of this thesis was to establish relationships between the ion content of isolated rat hepatocytes and metabolic processes such as glucose synthesis and fructose metabolism. In addition, a closely related subject, that of the mechanism of maintenance of the alleged ammonia gradient in liver, was also investigated. Isolated rat hepatocytes were separated from the incubation medium for estimation of intracellular ion and metabolite values. Cell volume was estimated both from wet weight, dry weight and inulin space of cells, and from distribution of tritiated water between cells and medium. Cell volume increased in conditions where intracellular accumulation of amino acids occurred and when cells were treated anaerobically. The specific inhibitor of the Na-K ATPase, ouabain, did not affect cell volume. Hepatocyte K+ and Na+ content, and K+ turnover, were estimated in conditions of added substrates such as fructose, lactate, NH4C1, ethanol, asparagine, glutamine and alanine. Change in turnover of cell K+, estimated with 42K+, was not directly related to change in rate of metabolic processes such as glucose or urea synthesis. However, in all conditions in which increased cell volume occurred and in which amino acids were accumulated, K+ turnover was increased. The effect of added alanine on cell ion and alanine content was examined in detail with special reference to the effects of ouabain and insulin. Metabolism of added fructose led to redistribution of cell and medium inorganic phosphate. Movement of phosphate was concomitant with change in intracellular K+ and Na+ content. Intracellular [ammonia] in isolated hepatocytes incubated without additions was 60 times greater than that of the medium. This constitutes an ammonia gradient only if intracellular ammonia was free in solution and not bound. Mechanisms which might be involved in maintaining high intracellular [ammonial] were investigated.